Conceptualization of Ontology of Return on Investment in Order to Generate It in Topic Map Standard - Dudycz, Helena (Konceptualizacja ontologii wskaźnika rentowności inwestycji w celu zapisania jej w standardzie mapy pojęć, 2010)
During the analysis of economic ratios, assessing an enterprise’s activity, information resulting from existing between them relations is essential. One of proposed solutions, which allows to show various connections (including semantic) between economic indicators, is topic map. Research on using topic map as a useful tool to organize the information in order to preserve the knowledge of economical ratios and semantic associations existing between them is carried out. In the paper the emphasis was put on conceptualization of ontology of return on investment (ROI) indicator. In order to build ontologically important terms, the classes, their hierarchy and relations were defined. The ontology of ROI indicator presented in the paper will be implemented in order to continue research on using standard of topic map to visualize semantic associations between indicators.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 87-100
Keywords: ontology of economic indicators; return on investment indicator; topic map